TESTOSTERON VE A VİTAMİNİNİN TAVŞANLARDA BAZI PIHTILAŞMA FAKTÖRLERİ, LİPİT PEROKSİDASYONU VE LİPİT PROFİLİ ÜZERİNE ETKİLERİ - AYDİLEK, NURETTİN (Fırat Üniveristesi, 2002)
Bu çalışmada, kastre, normal ve Have testosteron ile bunlara ek olarak E vitamini verilmesinin koagulasyon parametreleri, lipit peroksidasyonu ve lipit profili üzerindeki etkileri araştırıldı. Bu amaçla 46 erkek Yeni Zellenda tavşanı; 1. Kontrol (n=8), 2. Testostron (n=8), 3. Testosteron-E vitamini (n=8), 4. E vitamini (n=8), 5. Kastrasyon-E vitamini (n=7) ve 6. Kastrasyon grubuna (n=7) ayrılarak l0mg testosteron propionat ve 100 mg/kg dl-a tokoferil asetat 40 gün, günaşırı uygulanmıştır. Trombosit sayısı, kontrole göre 2. grupta artarken 6. grupta azalmıştır (p<0.05). E vitaminini trombosit sayısnı etkilememiştir. Kanama zamanı gruplarda farklılık göstermemiştir. Pıhtılaşma zamanı istatistiksel olmasa da 2. grupta kısalmıştır (p=0.068). 6. grupta 2. gruba kıyasla kanama ve protrombin zamanları uzamıştır (p<0.05). Kontrol grubuna kıyasla 2. grupta plazma MDA seviyesi artmış, 4. grupta ise MDA ve fîbrinojen konsantrasyonu azalmıştır (p<0.05). Kontrol ve 2. gruba kıyasla kastrasyon grubunda, total kolesterol seviyesi artmıştır (p<0.05). E vitamini lipit profilini etkilememiştir. HDL kolesterol seviyesi, 2. grupta düşerken 6. grupta yükselmiştir (p<0.05). LDL ve VLDL kolesterol seviyeleri değişmemiştir. HDL/LDL kolesterol oranı, kontrole kıyasla 2. grupta düşmüştür (p<0.05). Total kolesterol/HDL kolesterol oranı, kontrol ve kastrasyon grubuna göre 2. grupta artmıştır (p<0.05). Sonuç olarak testosteron, trombosit sayısı, plazma MDA seviyesi ve total kolesterol/HDL kolesterol oranını artırmış, HDL kolesterol ve HDL/LDL oranım ise azaltmıştır. Testosteron, koagulasyon ve protrombin zamanında istatistiksel olmasa da kısalmaya neden olmuştur. Testosteronun, MDA, fîbrinojen ve lipit profilindeki olumsuz etkileri sonucu hiperkoagulasyona neden olabileceği düşünülmektedir. E vitamini, plazma MDA ve fîbrinojen seviyesini azaltırken, lipit profili ve trombosit sayısını etkilememiştir. E vitamini, pıhtılaşma ve protrombin zamanlarını uzatma eğiliminde olduğundan yüksek dozlarında hipokoagulatif etki gösterebileceği tahmin edilmektedir.Testosteronun koagulasyon ve lipit profili üzerindeki olumsuz etkileri, E vitamini ilavesiyle anlamlı bir iyileşme ile sonuçlanmamıştır. Anahtar Kelimeler: E vitamini, testosteron, pıhtılaşma, lipit profili, lipit peroksidasyon

The aim of the study was to investigate the effects of testosterone and vitamin E on the haemostatic system, lipid profiles and lipid peroxidation levels in rabbits. For this purpose, 46 New Zelland White male rabbits were classifield to 6 groups as fallows; 1. Control (n=8), 2. Testosterone (n=8), 3. Testosterone- Vitamin E (n=8), 4. Vitamin E (n=8), 5. Castaration-Vitamin E (n=7) and 6. Castration (n=7) groups and were feed for 40 days. 10 mg testosterone propionate and 100 mg dl-cc tocopheryl acetate injected to animals every other day. The number of platelet was observed to increase in the 2nd group, was decreased in 6th group (p<0.05). Vitamin E administration did not change the platelet number. No significant differences were detected among groups in terms of bleeding time. While clotting time was shortened in the 2nd group, it was prolonged in the 6th group nonsignificantly. Prothrombin time was prolonged in the 4th group nonsignificantly. Prothorombin time was longer in the 6th group than in the 2nd group (p<0.05). Compared with control group, fibrinogen concentrations were lower in the 4th group (p<0.05). While MDA levels increased in the 2nd group, it decreased in 4th group (p<0.05). Total cholesterol value increased in the 6th group (p<0.05). There was no effect of vitamin E on lipid profiles. While HDL cholesterol value decreased in the 2nd group, it increased in the 6th group (p<0.05). No significant differences observed among all the groups in LDL and VLDL cholesterol levels. HDL cholestrol/LDL cholestrol ratio was decreased in the 2nd group (p<0.05), in contrast it was tended to increase in the 6th group (p>0.05). Total cholestrol /HDL cholesterol ratio increased in the 2nd group (p<0.05). This ratio was significantly higher in the 2nd group when compared with the 6ft group (p<0.05). In summary, it was observed that testosterone was able to increase the platelet number, plasma MDA levels and total cholesterol/HDL cholesterol ratio. Whereas it decreased HDL cholesterol and HDL cholesterol/LDL cholesterol ratio.It was observed that testosterone shortened the clotting time nonsignificantly. In the light of the results, testosterone may lead the hypercoagulation because it affects the oxidant-antioxidant balance and lipid profiles negatively. Vitamin E decreased fibrinogen and MDA levels, while there no effects on the lipid profile and platelet number. Bleeding and prothrombin time tended to prolonge in the 4th group. It was considered that high doses of Vitamin E may show hypocoagulative effects. It was observed that Vitamin E did not recover the negative effects of testosterone on the lipid profiles, MDA level and coagulation parameters. Key Words: Vitamin E, testosterone, coagulation, lipid profiles, lipid peroxidation
The Effects of testosterone and vitamin E on some coagulation factors, lipid peroxidation and lipid profiles in rabbits
Keywords: Fizyoloji; Physiology